A Comprehensive Comparison Study of Empirical Cutting Transport Models in Inclined and Horizontal Wells - Asep Mohamad Ishaq Shiddiq; Brian Christiantoro; Ildrem Syafrie; Abdurrokhim -; Bonar Tua Halomoan Marbun; Petra Wattimury; Hastowo Resesiyanto (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
In deviated and horizontal drilling, hole-cleaning issues are a common and complex problem. This study explored the effect of various parameters in drilling operations and how they affect the flow rate required for effective cutting transport. Three models, developed following an empirical approach, were employed: Rudi-Shindu's model, Hopkins', and Tobenna's model. Rudi-Shindu's model needs iteration in the calculation. Firstly, the three models were compared using a sensitivity analysis of drilling parameters affecting cutting transport. The result shows that the models have similar trends but different values for minimum flow velocity. Analysis was conducted to examine the feasibility of using Rudi-Shindu's, Hopkins', and Tobenna's models. The result showed that Hopkins' model is limited by cutting size and revolution per minute (RPM). The minimum flow rate from Tobenna's model is affected only by well inclination, drilling fluid weight and drilling fluid rheological property. Meanwhile, Rudi-Shindu's model is limited by inclinations above 45°. The study showed that the investigated models are not suitable for horizontal wells because they do not include the effect of lateral section.